Dispersion Characteristic of Spatiotemporal Sharply Autofocused Vector Airy-Circular Airy Gaussian Vortex Wave Packets - Li, Dong; Chen, Xin; Wei, Chengquan; Li, Peng; Zhao, Jianlin (Frontiers in Physics, 2021)
The spatiotemporal vector Airy-Circular Airy Gaussian vortex wave packet is constructed by solving the (3+1)D Schrodinger equation in free space. The wave packet can simultaneously autofocus in space and time by setting the appropriate initial pulse velocity  and the initial position of the main lobe T0. This kind of wave packet has low intensity before focusing, but the intensity at focus is about 80 times of the initial plane intensity. Our results may have potential applications in particle manipulation, laser processing, and other fields. Furthermore, the influence of the third-order dispersion coefficient on the evolution trajectory, the focus position, and the main peak intensity at the focus of the focusing pulse vector field is analyzed. The results show that the change of the initial velocity, the initial position, and the third-order dispersion coefficient can accurately control the evolution trajectory and the focus position, while the main peak intensity at the focus can only be controlled by adjusting the third-order dispersion coefficient. This means that the pulse vector light field can be manipulated precisely for precise processing by adjusting the third-order dispersion effect.